ACHIEVEMENT OF ANTENATAL CARE VISIT K4 PREGNANT WOMEN WITH THE SUPPORT OF HEALTH WORKERS: A LITERATURE REVIEW - Lili Jenni Suebu; Andi Nilawati Usman; Mardiana Ahmad (Institute for Research and Community Service of Health Polytechnic of Kerta Cendekia, Sidoarjo, 2022)
Background: Antenatal Care services are still a point of concern in efforts to improve the health and safety of mothers and babies. This service is not only of quantity but of the quality provided to pregnant women. The scope of K4 antenatal service visits in Papua Province is 29,149 pregnant women (37%); this is still far from the national target of 90%. Objectives: This study aimed to find out the influence of health worker support in achieving antenatal visits K4 in pregnant women using literature studies. Design: The method used in writing this article is a systematic review. Data Sources: Search for articles using Google Scholar were databased by entering the keyword